Participation of Trans-Women in Females' Sports Competitions: Fairness vs. Rights to Participating in Sports? - Taqwa, Muhamad Dzadit; Carofin, Valentino Rafael; Gloria, Stefanie; Tjiang, Alvin (UI Scholars Hub, 2024)
A trans-woman is someone who is biologically male at birth and then undergoes gender-affirming surgery, which can include genital feminization surgery, or may not undergo gender-affirming surgery but undergoes other therapies such as cross-sex hormone therapy or other physical organ surgeries apart from genital surgery, in order to be identified as a woman. The participation of trans-women in females' sports has sparked a debate, addressing issues of fairness on one side and transgender rights to participate in sports on the other. The fairness argument is based on the physical advantages that males have when competing against females. Generally, male athletes will outperform female athletes in most sports. On the other hand, the prohibition of trans-women from participating in females' sports is considered discriminatory and not respecting transgender individuals' right to participate in sports. This issue continues to be discussed because many female athletes complain about the presence of trans-women athletes in their competitions, as even rigorous training may not enable them to become champions. On the other hand, what solutions can be offered by the state to trans-women who want to become athletes? Through exploration in this article, the answer to this problem cannot be a gray area or middle ground but rather a choice between protecting women's rights in sports to excel or allowing trans-women the right to compete in the women's category; only one can be chosen. Alternatively, another option is to allow trans-women to compete in sports but in the new category, namely transgender category.